Partial Nephrectomy in a Patient with a Left Ventricular Assist Device - Jules P. Manger; John A. Kern; Tracey L. Krupski (Case Reports in Urology)
Left ventricular assist device (LVAD) use has increased as a bridge to heart transplant as well as destination therapy in patients with severe heart failure. Presence of LVAD is not a contraindication to noncardiac surgery but does present special challenges to the surgical, anesthesia, and cardiac teams. We present the case of a 40-year-old woman with idiopathic cardiomyopathy necessitating LVAD who underwent left partial nephrectomy for a renal mass. She had undergone three nondiagnostic percutaneous image-guided biopsies. Left partial nephrectomy was performed. Perioperative care was without incident due to careful oversight by a multidisciplinary team. Pathology revealed high-grade clear cell renal cell carcinoma (RCC) with negative margins. Polytetrafluoroethylene (PTFE) bolsters were misidentified six months postoperatively on computed tomography (CT) at an outside institution as a retained laparotomy sponge. This is, to our knowledge, the first report of a partial nephrectomy performed in a patient with LVAD.